Oral Administration of a New Copper (I) Complex with Coumarin as Ligand: Modulation of the Immune Response and the Composition of the Intestinal Microbiota in Onchorhynchus Mykiss - Guerrero-Nunez, J; Guerrero-Nunez, J; Modak-Canobra, B; Tello-Reyes, M; Soto-Aguilera, S; Arce-Ortega, P; Arce-Ortega, P; Vargas-Cardenas, R; Aldabaldetrecu-Urbieta, M; Aldabaldetrecu-Urbieta, M; Parra-Mardonez, N (Frontiers Media SA, 2024)
[Cu(NN1)2]ClO4 is a copper (I) complex, where NN1 is an imine ligand 6-((quinolin-2-ylmethylene) amino)-2H-chromen-2-one obtained by derivatization of natural compound coumarin, developed for the treatment of infectious diseases that affect salmonids. In previous research, we showed that the Cu(I) coordination complex possesses antibacterial activity against Flavobacterium psychrophilum, providing protection against this pathogen in rainbow trout during challenge assays (with an RPS of 50%). In the present study, the effects of administering [Cu(NN1)2]ClO4 to Oncorhynchus mykiss over a 60-days period were evaluated with regard to systemic immune response and its potential to alter intestinal microbiota composition. In O. mykiss, an immunostimulatory effect was evident at days 30 and 45 after administration, resulting in an increment of transcript levels of IFN-γ, IL-12, TNF-α, lysozyme and perforin. To determine whether these immunomodulatory effects correlated with changes in the intestinal microbiota, we analyzed the metagenome diversity by V4 16S rRNA sequencing. In O. mykiss, both [Cu(NN1)2]ClO4 and commercial antibiotic florfenicol had comparable effects at the phylum level, resulting in a predominance of proteobacteria and firmicutes. Nonetheless, at the genus level, florfenicol and [Cu(NN1)2]ClO4 complex exhibited distinct effects on the intestinal microbiota of O. mykiss. In conclusion, our findings demonstrate that [Cu(NN1)2]ClO4 is capable of stimulating the immune system at a systemic level, while inducing alterations in the composition of the intestinal microbiota in O. mykiss. © © 2024 Parra, Aldabaldetrecu, Arce, Soto-Aguilera, Vargas, Guerrero, Tello and Modak.